Investigating Substitutions in Antibody–Antigen Complexes Using Molecular Dynamics: A Case Study with Broad-spectrum, Influenza A Antibodies - Lees, William D.; Stejskal, Lenka; Moss, David S.; Shepherd, Adrian J. (Frontiers in Immunology, 2017)
In studying the binding of host antibodies to the surface antigens of pathogens, the structural and functional characterization of antibody-antigen complexes by X-ray crystallography and binding assay is important. However, the characterization requires experiments that are typically time consuming and expensive: thus, many antibody-antigen complexes are under-characterized. For vaccine development and disease surveillance, it is often vital to assess the impact of amino-acid substitutions on antibody binding. For example: Are there antibody substitutions capable of improving binding without a loss of breadth, or antigen substitutions that lead to antigenic escape? The questions cannot be answered reliably from sequence variation alone, exhaustive substitution assays are usually impractical, and alanine scans provide at best an incomplete identification of the critical residue-residue interactions. Here we show that, given an initial structure of an antibody bound to an antigen, molecular dynamics simulations using the energy method MM/GBSA can model the impact of single amino acid substitutions on antibody-antigen binding energy. We apply the technique to three broad-spectrum antibodies to influenza A hemagglutinin, and examine both previously characterized and novel variant strains observed in the human population that may give rise to antigenic escape. We find that in some cases the impact of a substitution is local, while in others it causes a re-orientation of the antibody with wide-ranging impact on residue-residue interactions: this explains, in part, why the change in chemical properties of a residue can be, on its own, a poor predictor of overall change in binding energy. Our estimates are in good agreement with experimental results – indeed, they approximate the degree of agreement between different experimental techniques. Simulations were performed on commodity computer hardware, hence this approach has the potential to be widely adopted by those undertaking infectious disease research. Novel aspects of this research include: the application of MM/GBSA to investigate binding between broadly-binding antibodies and a viral glycoprotein; the development of an approach for visualizing substrate-ligand interactions; and the use of experimental assay data to rescale our predictions, allowing us to make inferences about absolute, as well as relative, changes in binding energy.